A qualitative study exploring the experiences of parents of children admitted to seven Dutch pediatric intensive care units - Latour, Jos; van Goudoever, J.; Schuurman, B.; Albers, M.; van Dam, N.; Dullaart, E.; van Heerde, M.; Verlaat, C.; van Vught, E.; Hazelzet, J. (2011)
Purpose: To explore parents' experiences during the admission of their children to a pediatric intensive care unit (PICU). Method: Qualitative method using in-depth interviews. Thematic analysis was applied to capture parents' experiences. Thirty-nine mothers and 25 fathers of 41 children admitted to seven of the eight PICUs in university medical centers in The Netherlands were interviewed. Results: Parents were interviewed within 1 month after their child's discharge from a PICU. Thematic analysis identified 1,514 quotations that were coded into 63 subthemes. The subthemes were categorized into six major themes: attitude of the professionals; coordination of care; emotional intensity; information management; environmental factors; parent participation. Most themes had an overarching relationship representing the array of experiences encountered by parents when their child was staying in a PICU. The theme of emotional intensity was in particular associated with all the other themes. Conclusions: The findings provided a range of themes and subthemes describing the complexity of the parental experiences of a PICU admission. The subthemes present a systematic and thematic basis for the development of a quantitative instrument to measure parental experiences and satisfaction with care. The findings of this study have important clinical implications related to the deeper understanding of parental experiences and improving family-centered care.